2022
DOI: 10.6007/ijarbss/v12-i8/14050
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges Encountered by Mualaf After Conversion to Islam: A Study on The Apostasy (Murtad) Cases in Malaysia

Abstract: The rising of conversion mualaf to Islam proved that Islam has become a universal religion, and people started to recognize and accept the truth of Islam. Despite that, the phenomenon of mualaf returning to their former religion had concerned the authorities as reported by newspapers and social media. Even so, the issues related to mualaf have never ceased since it is a difficult matter to deal with it. Thus, the purpose of this study is to identify the reasons that caused mualaf to return to their former reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Source: Prepared by Authors (2024) In the context of Muslim reverts, as we all know, if non-Muslims desire to marry a Muslim partner, they must first adopt Islam before proceeding with the marriage. On that basis, it is not an exaggeration to claim that the majority of non-Muslims who convert to Islam do so exclusively for the sake of marriage (Rusli & Kadir, 2022). Despite that, considering that it is one of the many ways Allah SWT inspires non-Muslims to embrace Islam, the phenomenon does not seem to be inacceptable.…”
Section: Preservation Of Lineage/dignitymentioning
confidence: 99%
“…Source: Prepared by Authors (2024) In the context of Muslim reverts, as we all know, if non-Muslims desire to marry a Muslim partner, they must first adopt Islam before proceeding with the marriage. On that basis, it is not an exaggeration to claim that the majority of non-Muslims who convert to Islam do so exclusively for the sake of marriage (Rusli & Kadir, 2022). Despite that, considering that it is one of the many ways Allah SWT inspires non-Muslims to embrace Islam, the phenomenon does not seem to be inacceptable.…”
Section: Preservation Of Lineage/dignitymentioning
confidence: 99%
“…Previous studies have shown that Islamic affairs issues encompassed many aspects such as mosque management, Islamic education, family institutions, and zakat management. For instance, Rusli and Kadir [19] studied the reasons that caused new converts to return to their former religion due to lack of faith in Islam, insufficient knowledge of Islam, lack of religious commitment, marital issues, and conflict with their family. Additionally, Jusoh et al [20] identified seven main factors causing the low attendance of Muslims in the mosque, which are a limited function of the mosque, individual problems, inadequate basic facilities, non-strategic location, poor administrative and financial management as well as the personality of the mosque administrators.…”
Section: Introductionmentioning
confidence: 99%